Defining the Progression of Diabetic Cardiomyopathy in a Mouse Model of Type 1 Diabetes - De Blasio, Miles J.; Huynh, Nguyen; Deo, Minh; Dubrana, Leslie E.; Walsh, Jesse; Willis, Andrew; Prakoso, Darnel; Kiriazis, Helen; Donner, Daniel G.; Chatham, John C.; Ritchie, Rebecca H. (Frontiers in Physiology, 2020)
The incidence of diabetes and its association with increased cardiovascular disease risk represents a major health issue worldwide. Diabetes-induced hyperglycemia is implicated as a central driver of responses in the diabetic heart such as cardiomyocyte hypertrophy, fibrosis, and oxidative stress, termed diabetic cardiomyopathy. The onset of these responses in the setting of diabetes has not been studied to date. This study aimed to determine the time course of development of diabetic cardiomyopathy in a model of type 1 diabetes (T1D) in vivo. Diabetes was induced in 6-week-old male FVB/N mice via streptozotocin (55 mg/kg i.p. for 5 days; controls received citrate vehicle). At 2, 4, 8, 12, and 16 weeks of untreated diabetes, left ventricular (LV) function was assessed by echocardiography before post-mortem quantification of markers of LV cardiomyocyte hypertrophy, collagen deposition, DNA fragmentation, and changes in components of the hexosamine biosynthesis pathway (HBP) were assessed. Blood glucose and HbA1c levels were elevated by 2 weeks of diabetes. LV and muscle (gastrocnemius) weights were reduced from 8 weeks, whereas liver and kidney weights were increased from 2 and 4 weeks of diabetes, respectively. LV diastolic function declined with diabetes progression, demonstrated by a reduction in E/A ratio from 4 weeks of diabetes, and an increase in peak A-wave amplitude, deceleration time, and isovolumic relaxation time (IVRT) from 4–8 weeks of diabetes. Systemic and local inflammation (TNFα, IL-1β, CD68) were increased with diabetes. The cardiomyocyte hypertrophic marker Nppa was increased from 8 weeks of diabetes while β-myosin heavy chain was increased earlier, from 2 weeks of diabetes. LV fibrosis (picrosirius red; Ctgf and Tgf-β gene expression) and DNA fragmentation (a marker of cardiomyocyte apoptosis) increased with diabetes progression. LV Nox2 and Cd36 expression were elevated after 16 weeks of diabetes. Markers of the LV HBP (Ogt, Oga, Gfat1/2 gene expression), and protein abundance of OGT and total O-GlcNAcylation, were increased by 16 weeks of diabetes. This is the first study to define the progression of cardiac markers contributing to the development of diabetic cardiomyopathy in a mouse model of T1D, confirming multiple pathways contribute to disease progression at various time points.